Exploring experiences of ageing in older adults living with HIV in Sweden: a qualitative study - Annelie J. Sundler; Marie Lund; Sandra van Dulmen; Ewa Carlsson Lalloo (International Journal of Qualitative Studies on Health & Well-Being)
Purpose The number of people living and ageing with HIV is increasing. Insight into their well-being is lacking. The present study was conducted to explore needs, psychosocial issues and experiences of ageing in older adults living with human immunodeficiency virus (HIV) in Sweden. Methods A qualitative approach was employed. Semi-structured interviews were conducted with a convenience sample of 22 participants aged 65 years or older living with HIV in Sweden. Thematic analysis based on descriptive phenomenology was used. Results Being an older adult living with HIV emerged as a multifaceted experience. The meaning and impact of HIV varied from minimal to substantial, and ageing could overshadow the significance of HIV in everyday life. Three themes emerged: 1) increasing age in the foreground, 2) internalizing HIV in everyday life, and 3) socioemotional impact on everyday life. Conclusions The findings suggest a need for a more holistic approach to care of older adults living with HIV, recognizing the broader context of healthy ageing. While participants experienced good health, challenges related to ageing persist, and experiencing HIV-related stigma. The findings highlight the importance of empowering older adults living with HIV.